Implementing a quick Sequential (Sepsis-Related) Organ Failure Assessment sepsis screening tool: an interrupted times series study. (1st July 2020) - Alberto, Laura; Aitken, Leanne M; Walker, Rachel M; Pálizas, Fernando; Marshall, Andrea P
Abstract: Objective: The aim of this study was to evaluate the outcomes of implementing a sepsis screening (SS) tool based on the quick Sequential [Sepsis-Related] Organ Failure Assessment (qSOFA) and the presence of confirmed/suspected infection. The implementation of the 6-h bundle was also evaluated. Design: Interrupted times series with prospective data collection. Setting: Five hospital wards in a developing nation, Argentina. Participants: A total of 1151 patients (≥18 years) recruited within 24–48 h of hospital admission. Intervention: The qSOFA-based SS tool and the 6-h bundle. Main outcome measures: The primary outcome was the timing of implementation of the first 6-h bundle element. Secondary outcomes were related to the adherence to the screening procedures. Results: Of 1151 patients, 145 (12.6%) met the qSOFA-based SS tool criteria, among them intervention (39/64) patients received the first 6-h bundle element earlier (median 8 h; 95% confidence interval (CI): 0.1–16) than baseline (48/81) patients (median 22 h; 95% CI: 3–41); these times, however, did not differ significantly ( P = 0.525). Overall, 47 (4.1%) patients had sepsis; intervention patients (18/25) received the first 6-h bundle element sooner (median 5 h; 95% CI: 4–6) than baseline patients (15/22) did (median 12 h; 95% CI: 0–33); however, times were not significantly different ( P = 0.470). While intervention patients were screened regularly, only one-third of patients who required sepsis alerts had them activated. Conclusion: The implementation of the qSOFA-based SS tool resulted in early, but not significantly improved, provision of 6-h bundle care. Screening procedures were regularly conducted, but sepsis alerts rarely activated. Further research is needed to better understand the implementation of sepsis care in developing settings.